1995
DOI: 10.1016/s0022-5347(01)66718-1
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Clinical Guidelines Panel Summary Report on the Management of Clinically Localized Prostate Cancer

Abstract: In making its recommendations, the panel presented treatment alternatives as options, identifying the advantages and disadvantages of each, and recommended as a standard that patients with newly diagnosed, clinically localized prostate cancer should be informed of all commonly accepted treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
4

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(53 citation statements)
references
References 0 publications
0
49
0
4
Order By: Relevance
“…Primary organs at risk for severe side effects are the rectum (diarrhea, rectal bleeding and chronic proctitis) and the bladder/urethra (frequent micturition and inflammation at the prostate site) [4,6,10]. The frequency of late side effects does not differ from external beam irradiation [11,16,17,19]. In this study four patients (8%) suffered from grade III/IV side effects.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Primary organs at risk for severe side effects are the rectum (diarrhea, rectal bleeding and chronic proctitis) and the bladder/urethra (frequent micturition and inflammation at the prostate site) [4,6,10]. The frequency of late side effects does not differ from external beam irradiation [11,16,17,19]. In this study four patients (8%) suffered from grade III/IV side effects.…”
Section: Discussionmentioning
confidence: 54%
“…Although high-dose rate brachytherapy has been reported to be associated with a low frequency of severe side effects [17], it is not free from side effects. Primary organs at risk for severe side effects are the rectum (diarrhea, rectal bleeding and chronic proctitis) and the bladder/urethra (frequent micturition and inflammation at the prostate site) [4,6,10].…”
Section: Discussionmentioning
confidence: 99%
“…Radical prostatectomy is still the standard therapy option for localized prostate cancer in Germany. However, the American Prostate Cancer Guidelines Panel has analyzed all available literature data on radiation and surgical treatment series and concluded that "there was no clear-cut evidence for the superiority of any one treatment" [18]. For external beam radiation the survival rates were comparable with radical prostatectomy for similar stages [3].…”
mentioning
confidence: 99%
“…Besonders beim lokal begrenzten Prostatakarzinom zeigen internationale Studien, dass die Überlebenszeit unter verschiedenen Therapien durchaus vergleichbar ist [3], während sich die Nebenwirkungsprofile deutlich unterscheiden [4]. Gerade in diesen Fällen kann die Erhebung der gesundheitsbezogenen LQ dem Arzt und Patienten als eine wichtige Entscheidungshilfe für oder gegen eine bestimmte Therapie dienen.…”
Section: Originalien Hintergrund Und Fragestellungunclassified